Hmm, interesting
one way would be to multply it out or set it equal to 11x where x is a whole number (if x is not a whole number, then it is not divisible)
11x=7^6+7^5-7^4
undistribute 7^4
11x=(7^4)(7^2+7^1-1)
11x=(7^4)(49+7-1)
11x=(7^4)(55)
56=5*11
11x=(7^4)(5)(11)
divide by 11
x=5(7^4)
aka, find if 11 is a factor of that number
x=5(7^4)
Answer:
Step-by-step explanation:
Part A - Where did Phillip make a mistake? Justify your answer using complete sentences.
Use order of operation (PEMDAS)
He should multiply 8 x 4 first
Part B - Solve the expression correctly in the space below.
(5 x 9) - 8 x 4
= 45 - 32
= 13
Part C - Use the same rules of order of operations to solve the expression (8-4) +9 x 3. Explain your steps as you solve it.
(8-4) + 9 x 3
Step 1: 4 + 9 x 3 (Subtract in the parenthesis first)
Step 2: 4 + 27 (Multiply 9 x 3)
Step 3: 31 (Add)
Answer:
no
Step-by-step explanation:
6-6=0
1-6=-5
Answer:
Step-by-step explanation:
If we are given angles B and C, then all we have to do is add them together and then subtract that from 180 since all the angles of a triangle have to add up to equal 180.
62 + 48 = 110
180 - 110 = 70
Angle A = 70°